Nonminimal light-curvature couplings and black-hole imaging - Carballo-Rubio, Raúl; Delaporte, Héloïse; Eichhorn, Astrid; Fernandes, Pedro Goncalo da Silva (Physical review, 2025)
Nonminimal couplings between the electromagnetic field strength and the spacetime curvature are part of the effective field theory of gravity and matter. They alter the local propagation of light in a significant way if the ratio of spacetime curvature to the nonminimal coupling is of order one. Spacetime curvature can become appreciable around black holes, and yet the effect of nonminimal couplings on electromagnetic observations of black holes remains underexplored. A particular feature of the nonminimal coupling between the electromagnetic field-strength and the Riemann tensor is that it generates two distinct photon rings for different polarizations. Working within the paradigm of lensing bands and focusing on the 𝑛=1 lensing band, we illustrate by which diagnostics a modified light propagation may be distinguished from a modified spacetime geometry and how constraints on the value of the nonminimal coupling can be obtained.